The Role of Food Web Interactions in Multispecies Fisheries Management: Bio-economic Analysis of Salmon, Herring and Grey Seal in the Northern Baltic Sea - Lai, Tin-Yu; Lindroos, Marko; Grønbæk, Lone; Romakkaniemi, Atso (Kluwer Academic Publishers, 2021)
Multispecies bio-economic models are useful tools to give insights into ecosystem thinking and ecosystem-based management. This paper developed an age-structured multispecies bio-economic model that includes the food web relations of the grey seal, salmon, and herring, along with salmon and herring fisheries in the Baltic Sea. The results show that the increasing seal population influences salmon fisheries and stock, but the impacts on the harvest are stronger than on the stock if the targeted management policies are obeyed. If seal population growth and a low herring stock occur simultaneously, the salmon harvest could face a serious threat. In addition, scenarios of the multispecies management approach in this paper reveal a benefit that our model can evaluate the performance of different fisheries with identical or different management strategies simultaneously. The results show the most profitable scenario is that both fisheries pursuit aggregated profits and reveal a trade-off between herring fisheries and salmon fisheries. Our model indicates that the herring harvest level and the approaches to managing herring fisheries can influence the performance of salmon fisheries. The study also demonstrates a way to develop a multispecies bio-economic model that includes both migratory fish and mammalian predators.
Keywords: Bio-economic modeling; Dynamic optimization; Food web interaction; Grey seal (Halichoerus grypus); Herring (Clupea harengus); Multiobjective; Multispecies management; Salmon (Salmo salar)